Gymnema sylvestre – A Key for Diabetes Management – A Review (Pharmacology & Toxicology Research (ISSN 2349-4581), 2024)
Traditional medicines derived from medicinal plants are used by about 60 per cent world population. Diabetes is an important human ailment officiating many from various walk of life in different countries including India. It providing to a major health problem, especially in the urban area: Gymnema sylvestre R.Br. (Asclepiadaceae) is a herb distributed throughout the world. The leaves of the plant are widely used for the treatment of diabetes and as diuretic in India proprietary medicine. G. sylvestre, an Ayurvedic herb, came to be known as “destroyer of sugar” because, in ancient times, Ayurvedia physicians observed that chewing a few leaves of G. sylvestre suppressed the taste of sugar. It is used totally all over India for controlling blood sugar. Several bio-active compounds have been isolated from the herb for diabetes care. It is believed to be used in dyspepsia, constipation, jaundice, haemorrhoids, cardiopathy, asthma, bronchitis and leucoderma. A scrutiny of literature revealed some notable pharmacological activities of the plant such as anti diabetic, antiobesity, hypolipidaemic, antimicrobial, free radical scavenging and antiinflam-matory. The present review is an attempton various ethanobotanical and traditional uses, phytochemical and pharmacological approaches of G. sylvestre